Antioxidant Activity of Extract and Fraction from Boesenbergia pandurata Rhizome by FRAP Method - Kusumawati, Nursalinda; Haryoto, H (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Boesenbergia pandurata is one of the Zingiberaceae families found in Southeast Asia. In Indonesia, this plant which is known as “temu kunci” is widely cultivated by people everywhere included as home plant and used as family medicinal plant. B. pandurata contains flavonoid compounds which have the efficacy of being an antioxidant. Antioxidant is useful to overcome the negative effects of free radicals. Antioxidant test using the FRAP (Ferric Reducing Antioxidant Power) method began with B. pandurataextract using ethanol 96%, then continued with fractionation process of n-hexane, ethyl acetate, and ethanol. Free radical activity using spectrophotometry was seen with a wavelength of 712 nm and the total antioxidant value was calculated based on the absorbance of each samples. The result of study of antioxidant activity from ethanol extract, non-polar, semi-polar, and polar fraction were 37.59; 27.43; 32.93; and 35.68 mgAAE/g.